Historia de los gabinetes de comunicación en España - Almansa Martínez, Ana (Historia y Comunicación Social, 2004)
In the last decades, the communication has been acquiring social relevancy. Facing a new model of society— «society of the information», «society of the knowledge»—, needs in communication have grown to an almost dizzy pace. So that, nowadays, any organization that boasts must take care of its communication, of what it transmits to its clients. Undoubtedly, these needs of considerable importance in the current society were unimaginable a few decades ago. Communication offices have prospered around the whole Spanish geography in the last years, and have increased their tasks as well. Although in the beginning their responsibility just consisted of relations with mass media, as time goes by their duties have branched out. So that, nowadays, is more appropriate to express in terms of communication offices instead of only press offices. Of this historical evolution in Spain treats this chapter.